Athar Jā’ihat Corona ‘alā Marākiz al-Lughāt wat Tadrīb al-Khāssah bi Mālīziyā: al-Akādimiyyah al-Dawliyyah lil Lughāt wat Tadrīb wat Tarjamah bi Kuala Lumpur Namuzajan - Abdul Rahman Bin Chik; Khalid Chtaibi; Muhammad Amiruddin al Kholidi (Tarling : Journal of Language Education, 2022)
None had predicted the amount of the recession that is caused and still by the Coronapandemic, and its disastrous effects on all areas of work around the world. Among thevital sectors hit by the pandemic are private language and training institutes that were notprepared for this invasion, as it paralyzed their performance. Vision InternationalAcademy ranked an advanced position in the educational and training arena in Malaysiafor 10 years, but its record declined due to the constraints of Corona. The paper is one offew scientific studies that dealt with this phenomenon in a country like Malaysia, which isconsidered a leading educational hub in the region and the world, by adopting thedescriptive analytical approach as it is the most appropriate in dealing with the nature andrequirements of this study, and focused on exploring the depths of this phenomenon,starting with a review of the bright history of the Academy as a model before Corona, thendiscussing and analyzing the causes of stagnation and its manifestations, and ending withdissecting the data and results to extract conclusions, recommendations and proposals thatthe researcher submits to all the players in the education system in language and traininginstitutes to remedy the negatives and avoid what happened in the future.